Hypothesized behavioral host manipulation by SARS-CoV2/COVID-19 infection. (August 2020) - Barton, Michael C.; Bennett, Kaylee V.; Cook, John R.; Gallup, Gordon G.; Platek, Steven M.
Abstract: Although not widely studied, behavioral host manipulation by various pathogens has been documented. Host manipulation is the process by which a pathogen evolves adaptations to manipulate the behavior of the host to maximize reproduction (Ro ) of the pathogen. The most notable example is rabies. When a host is infected with the rabies virus it gets into the host's central nervous system and triggers hyper aggression. The virus is also present in the rabid animal's saliva so being bitten transmits the infection to a new host and the old host is left to eventually die if untreated. Toxoplasmosis is another example. When mice are infected they demonstrate a fearlessness toward cats, thus increasing their chances of being eaten. Toxoplasmosis needs the digestive tract of the feline to survive. Recent studies have shown that exposure to toxoplasmosis in humans (e.g., through cat feces) has also been associated with behavioral changes that are predicted to enhance the spread of the pathogen. Even the common influenza virus has been shown to selectively increase in-person sociality during the 48-hour incubation period, thus producing an obvious vector for transmission. Here we hypothesize that the novel coronavirus, SARS-CoV2, which produces the COVID-19 disease may produce similar host manipulations that maximize its transmission between humans.